Sliding mode control with open‐switch fault diagnosis and sensorless estimation based on PI observer for PMSM drive connected with an LC filter. Issue 11 (18th June 2020) - Wang, Minghui; Xu, Yongxiang; Zou, Jibin
Abstract : In some cases, LC filters are installed between the inverters and motors to suppress the adverse effects of pulse width modulation. However, some techniques should be modified, because the mathematical model of the drive system is changed by the LC filter and the sensors on the inverter output cannot measure some necessary variables. In this study, a multi‐purpose proportional‐integral (PI) observer is proposed at first. The type of observer depends on whether the position sensor is equipped. A sliding mode controller for the LC filter based on the observer is presented, therefore improving the dynamic performance. Furthermore, if the position sensor of the rotor is equipped, an open‐switch fault diagnostic method is realised by means of the PI observer; if the position sensor is not equipped, the sensorless estimation is realized. The proposed strategies were realised without any additional current/voltage sensors. Experimental results verified the effectiveness of the proposed strategies.